2018
DOI: 10.1016/j.placenta.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight to placenta weight ratio and its relationship to ultrasonic measurements, maternal and neonatal morbidity: A prospective cohort study of nulliparous women

Abstract: BWPW-ratio is related to ultrasonic measurements and both neonatal and maternal morbidity. Therefore, this ratio may be an indicative marker of immediate and longer term health risks for an individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
0
37
1
Order By: Relevance
“…Ratios and residuals were also lower in newborns with lower Apgar scores and reduced prospects of postnatal survival. Previously, fetal death has been found to be associated with very high and very low BW:PW ratio preterm, and very high BW:PW ratio at term [16] whereas a recent study found that low BW:PW ratio at term was associated with neonatal morbidity (defined in terms of low Apgar score, metabolic acidosis and/or admission to the neonatal unit) [17]. In the present study, residuals almost always showed differences at least as great as the BW:PW ratio in terms of the magnitude of difference between placentas with and without pathology, or between adverse and normal outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Ratios and residuals were also lower in newborns with lower Apgar scores and reduced prospects of postnatal survival. Previously, fetal death has been found to be associated with very high and very low BW:PW ratio preterm, and very high BW:PW ratio at term [16] whereas a recent study found that low BW:PW ratio at term was associated with neonatal morbidity (defined in terms of low Apgar score, metabolic acidosis and/or admission to the neonatal unit) [17]. In the present study, residuals almost always showed differences at least as great as the BW:PW ratio in terms of the magnitude of difference between placentas with and without pathology, or between adverse and normal outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Placental weight was obtained from medical records and measured according to standard protocols [15]. Birth weight:placental weight ratio was calculated, as indicator of the ability of the placenta to maintain adequate nutrient supply to the fetus, and is associated with neonatal morbidity and mortality [16]. Small-size for gestational age (SGA) was defined as gestational age adjusted birth weight <10th percentile.…”
Section: Placental Vascular Function and Placental Weight At Birthmentioning
confidence: 99%
“…Research showed that not only the size and weight of the placenta, but also the weight of the placenta in relation to birth weight was associated with both umbilical and uterine artery PI (Salavati et al, 2018). Specifically, high BWPW-ratio was associated with both higher umbilical artery PI (26 weeks of gestation) and higher uterine artery PI (20 weeks of gestation), two markers of decreased placental function.…”
Section: Clinical Relevance Of Antenatal and Postnatal Assessment Of mentioning
confidence: 99%
“…Specifically, high BWPW-ratio was associated with both higher umbilical artery PI (26 weeks of gestation) and higher uterine artery PI (20 weeks of gestation), two markers of decreased placental function. Low BWPW-ratio was not associated with either umbilical or uterine artery PI, however it was with maternal and neonatal morbidity (Salavati et al, 2018). Decreased placental function may sound contradictory, since placentas in the group of high BWPW-ratio can also be seen as very efficient.…”
Section: Clinical Relevance Of Antenatal and Postnatal Assessment Of mentioning
confidence: 99%